Association of joint erosion with SLC22A4 gene polymorphisms inconsistently associated with rheumatoid arthritis susceptibility. (August 2015) - Han, Tae-Un; Lee, Hye-Soon; Kang, Changwon; Bae, Sang-Cheol
Abstract Two single-nucleotide polymorphisms (SNPs) in SLC22A4 encoding an organic cation/zwitterion transporter protein, rs2073838 (commonly called slc2F1) and rs3792876 (slc2F2), had been associated with susceptibility to rheumatoid arthritis (RA) in two Japanese and one recent Chinese studies but not in other two Japanese and six Caucasian studies. In this study, the two SNPs were genotyped for 2313 Korean participants and their associations with RA susceptibility and severity were examined. SNP association with RA susceptibility was tested among 1304 RA patients and 1009 healthy controls, and association with joint erosion among 1063 erosive and 241 non-erosive RA patients. Meta-analysis for RA susceptibility association was additionally performed using 10 previous studies and the current one. The two SNPs were almost perfectly correlated with each other (r2 = 0.98), and therefore only slc2F1 was tested for association. RA susceptibility association was not found in Koreans (p = 0.93), but still significant in meta-analysis of six Asian studies including this Korean study (p = 0.00036, odds ratio = 1.1) or all 11 studies additionally including five Caucasian studies (p = 0.00021, odds ratio = 1.1). In contrast, an association was found for RA severity in Koreans. The minor allele A was marginally associated with 1.5-fold increased risk of joint erosion among RA patients afflicted for ≤11 years (p = 0.025) or ≤7 years (p = 0.029), though not among patients with longer-standing RA. Accordingly, SLC22A4 was associated with joint erosion in not-very-longstanding RA, although RA susceptibility association was weak and its clinical significance was uncertain.